Paintings above the doorway in the exterior walls of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Paintings above the doorway in the exterior walls of the Bhandasar Temple. There are two sets of paintings, each consisting of a central rectangular block flanked by square blocks. The lower set has the painting of Murlidhara Krishna at the centre with two attendants in the flanking squares. Similarly, the upper set is a painting of Hanuman at the centre, carrying the mountain of Sanjeevani. Murlidhara Krishna is shown as blue-skinned wearing a pitambar (yellow lower garment).